Enhancing Critical Thinking and Problem-Solving Skills of Accounting Students at Sorsogon State University – Bulan Campus: Evidence-Based Strategies for Improving Licensure Examination for Certified Public Accountants (LECPA) Performance - Atty. Michael B. Bongalonta; Michelle M. Bongalonta; Diana V. Sales (Future Science / FSH-PH Publications, 2026)
This study aimed to assess the critical thinking and problem-solving skills of accounting students at Sorsogon State University – Bulan Campus and explore evidence-based strategies to enhance these competencies for improved performance in the Licensure Examination for Certified Public Accountants (LECPA). Specifically, the study sought to (1) review and analyze the CPALE performance ratings of accounting graduates, (2) assess the current level of critical thinking and problem-solving skills, and (3) identify strategies to strengthen these skills and improve licensure outcomes. A mixed-methods descriptive-evaluative research design was employed. Quantitative data were gathered from pre- and post-assessments of students’ critical thinking and problem-solving skills, as well as official CPALE results from 2016 to 2024. Qualitative data were obtained through structured interviews and surveys of purposively sampled accounting faculty, program administrators, and students who had taken the CPA board examination. Quantitative analysis measured competency levels, while thematic analysis of qualitative data identified patterns regarding the effectiveness of evidence-based strategies. Findings revealed that accounting students’ critical thinking and problem-solving skills are moderate, with a mean score of 62%, reflecting gaps in higher-order cognitive competencies necessary for licensure success. CPALE performance exhibited significant fluctuations over the years, highlighting systemic challenges in preparing students for professional practice. Evidence-based interventions including enhancement and tutorial classes, technology-based learning, curriculum and policy enhancements, financial and moral support, strict retention policies, benchmarking with top-performing schools, and regular qualifying examinations were reported by students, faculty, and administrators to improve analytical reasoning, application skills, and exam readiness.